Optimization of a natural fermentative medium for submerged mycelial culture of Ganoderma lucidum and the nutritional and bioactive composition of the cultured food-grade mycelia - Shizhong Zheng; Lu Zhang; Yihui Yang; Shengrong Liu; Qi Wei; Qianhui Huang; Weirui Zhang (PLoS ONE, 2026)
Ganoderma lucidum is a famous traditional Chinese medicinal fungus with health-promoting and pharmacological properties. The present study aimed to provide a liquid medium for G . lucidum submerged fermentation suitable for safely utilizing the mycelia and broth and as a solution to potentially improve the process’ economy. For this, a natural medium was formulated and optimized. The nutritional and bioactive composition of the mycelia cultivated in the optimized medium and a nutrient-rich (NR) medium were also determined. The one-variable-at-a-time experiments indicated that among various tested carbon sources, sucrose was favorable for mycelial growth. The supplementation of corn flour in the medium promoted mycelial growth and its optimal level was 7.0 g/L. A further study by response surface methodology obtained an optimal medium comprising of 300 g/L potato (use its extract), 25 g/L sucrose, and 7.5 g/L corn flour. Using the optimized medium, the mycelial yield reached 7.51 g/L. The crude ash (10.43%) and fiber (10.51%) content of the mycelia cultivated in the optimal medium was higher than those (ash 5.75% and fiber 5.93%) of the mycelia grown in the NR medium, while the proteins content and all examined amino acids were lower than those of the mycelia cultivated in the NR medium. The mycelia contained 32.24 mg/g triterpenoids and 3.42% intracellular polysaccharides, which is higher than those (triterpenoids 20.35 mg/g and intracellular polysaccharides 2.03%) of the mycelia cultivated with the NR medium. These findings indicated that the cultured food-grade mycelia had the potential for use in the pharmacological industry. Meanwhile, the broth had the potential for safe use in foods due to free of chemicals. The present study provides a reference for improving the economy of G . lucidum submerged culture by using a natural medium, and its industrial fermentation may be economically viable.